ETNOGRAFI DAYA MAGIS KERIS PUSAKA - Stefanus Rudyanto (Lakon : Jurnal Kajian Sastra dan Budaya, 2015)
Keris pusaka or heirloom keris is a heritage of culture from Indonesia. Speaking about keris pusaka, there are some perspectives, they are, philosophy, art, and magical power inside of it. This research is using ethnography methodology to comprehend the magical power in keris pusaka. The steps of methodology are similar to James P. Spradley’s that applied as grand theory in order to elaborate keris’ magical power with its abstract ambience. This research is reveals pengagem’s in various perspectives toward their keris pusaka and its magical power.